2020
DOI: 10.1136/bmjopen-2020-042072
|View full text |Cite
|
Sign up to set email alerts
|

Senior ambulance officers in Swedish emergency medical services: a qualitative study of perceptions and experiences of a new management role in challenging incidents

Abstract: ObjectivesIncreased demands are placed on emergency services and their role and ability to act in incidents in challenging environments, for example, road tunnels. Collaboration between officers from emergency services (fire brigade, police and ambulance services) is important for an effective rescue effort. In Gothenburg, Sweden, a position as a senior ambulance officer (SAO) within the emergency medical services (EMS) has been introduced to support the regular force during major incidents. The aim of this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…They all operate on different RFAs, having to relate to different boundaries stated by their own organizations, professional regulations, and applicable laws. Previous research on collaboration in the EMS in general, has often focused on time-sensitive emergencies, 36 or work with hospitals 37 but has paid less attention to low-priority missions. This study indicates that clinicians and ORs believe that EMS positioning in relation to possible collaborators needs strengthening to enable clinicians to act based on their CR.…”
Section: Discussionmentioning
confidence: 99%
“…They all operate on different RFAs, having to relate to different boundaries stated by their own organizations, professional regulations, and applicable laws. Previous research on collaboration in the EMS in general, has often focused on time-sensitive emergencies, 36 or work with hospitals 37 but has paid less attention to low-priority missions. This study indicates that clinicians and ORs believe that EMS positioning in relation to possible collaborators needs strengthening to enable clinicians to act based on their CR.…”
Section: Discussionmentioning
confidence: 99%
“…In Norway, which has more than a thousand road tunnels, emergency services have developed specific tunnel-incident rescue strategies (Hylander et al, 2019). Hylander et al (2019Hylander et al ( , 2020 found that the most critical factor in their success was collaboration, beginning with on-scene commanders' decision-making, tactical support and prehospital care. Other studies have confirmed the importance of collaboration among various organisations, such as RS, police, emergency dispatch centres (EDCs) and infrastructure owners (Alvear et al, 2013;Bj€ ornstig and N€ asman, 2017;Nj a and Svela, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Hylander et al. (2019, 2020) found that the most critical factor in their success was collaboration, beginning with on-scene commanders' decision-making, tactical support and prehospital care. Other studies have confirmed the importance of collaboration among various organisations, such as RS, police, emergency dispatch centres (EDCs) and infrastructure owners (Alvear et al.…”
Section: Introductionmentioning
confidence: 99%